Hubungan Peran Perawat Dalam Merawat Pasien Dengan Resiko Infeksi Post Operasi Di Rumah Sakit Dkt Sidoarjo - Reni Apriliyana (Journal of Nursing Perspectives, 2025)
Postoperative infection remains a significant challenge in hospital settings and contributes substantially to patient morbidity, prolonged length of stay, and increased healthcare costs. Nurses play a pivotal role in preventing postoperative infections through comprehensive and consistent nursing care practices. This study aimed to examine the relationship between nurses’ roles in caring for postoperative patients and the risk of postoperative infection at DKT Hospital Sidoarjo. A descriptive analytical study with a cross-sectional design was conducted involving 30 nurses who were directly involved in postoperative patient care. Total sampling was applied to ensure comprehensive representation. Data were collected using structured questionnaires and observation sheets that assessed nursing roles, including monitoring vital signs, wound management, early mobilization, rehabilitation support, and discharge planning. Bivariate analysis was performed to determine the relationship between nursing roles and postoperative infection risk. The results demonstrated a statistically significant relationship between the role of nurses and the risk of postoperative infection (p = 0.038), indicating that optimal nursing performance is closely associated with lower infection risk. These findings highlight that effective nursing care, delivered through professional competence, vigilance, and holistic patient-centered approaches, is essential in supporting postoperative recovery and preventing complications. The study underscores the importance of strengthening nursing roles through continuous education, institutional support, and policy alignment to enhance quality of care. Empowering nurses to practice evidence-based postoperative care is not only beneficial for patient outcomes but also contributes to overall healthcare quality improvement. This study provides valuable insights for nursing practice, hospital management, and future research focusing on infection prevention strategies within postoperative care settings.